Is Technology Historically Independent of Science? A Study in Statistical Historiography - Price, Derek J. de Solla (1965)
p. 558: “There is little doubt that such subjects as particle physics and molecular biology would be on the top of that scale and the taxonomic biological sciences toward the bottom. One might well find, however, that Assyriology and some parts of history, economics, and linguistics might be near the top, while other parts of history were near the bottom.”